Pediatric Preventive Care in Middle-High Resource Countries—The Padova Chart for Health in Children - Galderisi, Alfonso; Perilongo, Giorgio; Caprio, Sonia; Da Dalt, Liviana; Di Salvo, Giovanni; Gatta, Michela; Giaquinto, Carlo; Rizzuto, Rosario; Robb, Adelaide; Sly, Peter David; Simonelli, Alessandra; Staiano, Annamaria; et al. (Frontiers in Pediatrics, 2022)
Importance: The Padova Chart for Health in Children (PCHC) aims to gather the evidence of healthcare promotion and protection for children (i.e., aged <18 y) into a single document in order to guide families, healthcare providers and social actors on healthy choices. No more than 2% of Europeans and north Americans aged <30 y have a healthy lifestyle. This, together with metabolic and brain plasticity during childhood, creates the ideal opportunity to implement preventive strategies. Guided interventions promoting healthy lifestyle in children and families therefore have a key role in abating the unprecedented pandemic of noncommunicable diseases (NCDs) in adulthood. Observations: The PCHC is divided into four sections: nutrition, cardiovascular health, respiratory health, and mental and social health. Each section is structured in an ALICE approach (assessment, lobbying, intervention, call-for-action, evaluation): assessment of necessity, describing relevance to healthcare; lobbying to identify those who can effect the proposed interventions; interventions involving family, school and peers; a call-for-action to define priorities among the proposed interventions; and objective evaluation measures that can be applied on a population basis. Conclusions and Relevance: Interventions promoting health in childhood require joint action from multiple institutional, local and family representatives, with the shared goal of promoting health across the entire age group. These lifestyle interventions have the potential to change the lifetime risk trajectory for NCDs.